Geographic and altitudinal range extension of Oreobates amarakaeri Padial et al., 2012 (Anura: Craugastoridae) - Ttito, Alex; Catenazzi, Alessandro (Zootaxa, 2019)
The genus Oreobates Jiménez de la Espada (1872) is monophyletic, and currently 24 species of Oreobates have been named (Köhler & Padial, 2016). Oreobates distributed from southern Colombia to central Brazil and northwestern Argentina (Köhler & Padial, 2016; Teixeira, Amaro, Recoder, De Sena, & Rodrigues, 2012). Most species of Oreobates occur in the cloud and montane forests of the tropical and subtropical Andes from Ecuador to Argentina (Padial et al., 2012). Padial et al., (2012) described Oreobates amarakaeri with two specimens collected in 2008 between 685–1000 m a.s.l. in Distrito Camanti, Quispicanchis Province, Department of Cusco, Peru (Figure 1). Herein we report four additional specimens of O. amarakaeri, extending its distributional and altitudinal ranges in southern Peru. We collected specimens during our surveys in the Departments of Cusco and Puno.